112 Inability to exercise or a non-diagnostic exercise test identify a higher risk sub-set of patients in those with an intermediate pretest probability of coronary artery disease. (22nd September 2015) - Nair, S B; Chacko, S M; Hamid, T; Turkie, W; Rezai, R; Khattar, R S
Abstract : Introduction: The Rapid Access Chest Pain (RACP) service model aims to fast-track all patients with suspected cardiac chest pain using exercise electrocardiography. However, in those with an intermediate pre-test probability of coronary artery disease, guidelines recommend non-invasive stress imaging as the preferred first line investigation. The non-invasive functional imaging techniques include stress echocardiography and radionuclide myocardial perfusion imaging, but in many centres these investigations are not readily available and so the exercise ECG remains the mainstay investigation. Aims: This was a study of patients attending the RACP service with an intermediate pre-test probability of CAD (Int-CAD). The aims were to compare the demographic characteristics of those with and without a non-diagnostic exercise ECG and to determine the independent predictors of all-cause death in this group of patients Methods: We retrospectively studied consecutive patients who attended the RACP service from January 2004 to December 2006. The variables analysed included age, gender, ethnicity, diabetes, hypertension, hypercholesterolaemia, smoking and exercise ECG findings. Three year follow-up data on all-cause death were collected from the hospital system and central register. Results: The study cohort consisted of 1174 patients with an intermediate pretest probability of CAD. The patients were divided into two groups; group 1 consisted of those with a diagnostic exercise ECG (either positive or negative), and group 2 were those without a diagnostic test (either an equivocal result or unable to exercise). Comparative data of the two groups are shown below: Group 2 patients were significantly older, had a higher proportion of women, higher prevalence of diabetes, hypertension and hypercholesterolaemia and a higher pre-test probability of CAD. Over a mean follow up period of 39.4±9.9 months, the death rate in group 1 was 1.5% and in group 2 was 7.5%. Multivariate analysis showed that age (p<0.01), diabetes (p<0.01) and a non-diagnostic exercise ECG (p<0.01) were independent predictors of death. Conclusion: In conclusion, a non-diagnostic exercise ECG identifies a higher risk sub-set of patients (29% of patients) in the intermediate pretest probability group with a fivefold increased risk of death at 3 years. This latter sub-set of patients, in particular, is not adequately well served by the RACP service model based on the exercise ECG. Future models of care need to incorporate early and increased access to pharmacological stress imaging.